Applied principles of hydrology - Manning, John C. (John Craige), 1920- (Upper Saddle River, N.J. : Prentice Hall, 1997)
This book contains: The Water cycle; The Structure and Properties of Water; Water in the Air: Evaporation and Condensation; Precipitation; Infiltration and Soil Water; Evapotranspiration; Groundwater; Runoff; Chemical Quality of Natural Water; and The Water Cycle and Man.
Keywords: Hydrology; Hydrology